Foreign Direct Investment in Emerging Markets : Income, Repatriations and Financial Vulnerabillities - Lehmann, Alexander (Washington, D.C. : International Monetary Fund, 2002)
Based on U.S. data, the returns on foreign direct investment in emerging markets are shown to be substantially higher than would be suggested by official balance of payments statistics. This paper identifies the determinants of FDI profitability in 43 industrialized and developing countries. After financial leverage and the effect of tax minimizing income transfers are controlled for, host country risk and market openness are found to raise affiliate returns on equity and returns on sales. In the context of a number of financial crises during the 1990s, income repatriations are shown to be pro-cyclical, though the effect of host country recessions is mitigated through continued spending on fixed capital and a re-direction of affiliate sales towards export markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet